(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The main requirement of the modern educational process is to form an independent thinker, able to communicate, and able to analyze complex problems. Critical thinking and problem-based learning (PBL) methods play an important role in the development of such competencies. The formation of communicative skills is not limited to knowledge of the language, but also includes the ability to clearly express thoughts, ask questions, discuss, argue, and make decisions. From this point of view, this study highlights the role of critical thinking and PBL approaches in the development of communicative competence.